Field-Effect Transistors for Biomedical Applications - Fernandes, Edson Giuliani Ramos; Faria, Henrique Antonio Mendonça [UNESP]; Vieira, Nirton Cristi Silva (Springer Nature, 2022)
Field-effect transistors are devices suitable for applications in bioelectronics, because of their small size, high signal-to-noise ratio, and the possibility of using biocompatible and flexible materials in device design. Since the introduction of the ion-sensitive field-effect transistor (ISFET) by Bergveld, various types of FETs are applied as transducers for the development of biomedical devices. These include the ISFET and its derivatives, such as the extended gate field-effect transistors (EGFETs), the organic field-effect transistors (OFETs), nanomaterial-based field-effect transistors (NanoFETs), and the tunnel field-effect transistors (TFETs). In this chapter, we highlight FET devices for biomedical applications. A description is made of the application of FETs directly with biological systems, including biosensors, interfaces with cells and tissues, and other biomedical applications. We also provide challenges and perspectives for this fascinating technology.
Keywords: Bioelectronics; Biosensor; Field-effect transistor; Transduction